Terra sem história : identidade e história na Amazônia de Euclides da Cunha - Silva, Célio Leandro da (2015)
This work is focused analyze aspects related to the presence of Euclides da Cunha in the Amazon. We sought to investigate the genesis of border conflicts between Brazil and Peru, determining factor for the realization of the Joint Commission on Recognition of Headwaters of the Purus River, which led Euclid. In general, these conflicts were the result of disputes over rich producing rubber regions. As a result of this trip, the writer left recorded a set of information relating to matters related to hydrography, geomorphology, climate and especially on Amazonian man. Such impressions resulted in the compilation of the work the Fringes of History, a posthumous book that brings together the Euclidean texts on Amazon and has become the centerpiece of this dissertation research. The aim, above all, to understand the way the author of The Barrens portrayed the Amazon from their experience on the spot, which contributed to bring the light of science Earth Without History - Amazon - and that gives the Euclides da Cunha title of one of the greatest interpreters of the partners questions of Brazil.